Pyridinium salts: from synthesis to reactivity and applications - Subbiah Sowmiah; José M S S Esperança; Rebelo, Luís P N; Afonso, Carlos A M (Organic chemistry frontiers an international journal of organic chemistry, 2018)
Structurally diverse pyridinium salts are quite familiar structures in many natural products and bioactive pharmaceuticals. Over the centuries, these privileged scaffolds have played an intriguing role in a wide range of research topics and, thus, this review aims at highlighting the pyridinium salts in terms of their synthetic routes, reactivity and their importance as pyridinium ionic liquids, as pyridinium ylides, as anti-microbial, anti-cancer, anti-malarial and anti-cholinesterase inhibitors, as well as their applications in materials science and biological issues related to gene delivery.